THE UTILIZATION OF DIGITAL TECHNOLOGY IN ISLAMIC RELIGIOUS EDUCATION LEARNING AT QURRATA A’YUN KINDERGARTEN - Mariani, Mariani; Aprilia, Nurul; Rahimah, Rahimah; Zulaikah, Eni; Cahyadi, Ani (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
This research explores the utilization of digital technology in learning Islamic Religious Education (PAI) at Qurrata A’yun Kindergarten, Banjar Regency. Employing a qualitative approach, data were obtained through interviews, observations, and documentations. The results showed that the use of digital technology, such as Power Point presentations (PPT), animated videos, and audio, were able to increase students’ interest and motivation. The material that displayed about Islamic learning such as the story of prophet and the congregational prayer. Teachers play a central role in this process, although there was obstacles such as limited infrastructure and technological competence for senior teachers. Its challenges include the need for additional time for technology integration and maintaining a balance between digital and conventional learning. This study suggested that there must be technology training for teachers, procurement of adequate supporting facilities, and development of a digital-based curriculum that remains integrated with Islamic values.